Teaching Serious Issues through Player Engagement in an Interactive Experiential Learning Scenario - Schoenau-Fog, Henrik (Eludamos, 2012)
In order to inform about a serious subject concerned with the tragic consequences of being a victim of war in an interactive narrative game-like experience, it is essential to design a scenario which engage the participants despite the grave content. This paper thus focuses on how player engagement and playfulness can be applied to drive participants through a non-pleasurable experiential learning scenario in order to communicate serious topics. By investigating the concept of engagement in games, a framework of player engagement will be described. The framework has been used in a case-study to aid the design of an application – the “First Person Victim” – which is intended to be used in combination with an in-class discussion in order to address the serious topic. An evaluation of the scenario indicated that theme related feelings like hopelessness, fear, loneliness, and chaos are experienced by engaged participants and that there is a potential for using the scenario as a tool in teaching.